Eksperimentasi Model Pembelajaran Jigsaw Puzzle Map Terhadap Prestasi Belajar Matematika Materi Himpunan Ditinjau dari Tipe Kepribadian Siswa Kelas VII Semester 1 MTsN 1 Bojonegoro Tahun Ajaran 2015/2016 - Anis Umi Khoirotunnisa’ (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2017)
The research was conducted with the aim to determine: (1) which one results better mathermatics learning achievements between Jigsaw puzzle map and conventional learning model, (2) wich one results better mathematics learning achievements student with rational personality type, idealist personality type, guardian personality type, and artisan personality type in solving mathematics problems, (3) whether there is an interaction between learning model and the type of personality to the mathematics achievement of students.it was quantitative with quasi experimental research. The subject of this research was taken by using a cluster random sampling. The subject of this research 70 student of the seven grade whom come from 2 class students at MTsN I Bojonegoro. The techniques of collecting the data in this research were questionnaire and written test. The result of this eksperiment is : (1) jigsaw puzzle map learning model are better than convenstional learning model. (2) personality type give effect in mathematics learning achievements student, (3) there is no interaction between learning model ang the type of personality to the mathematics achievent students.